A Philadelphia Perspective The Civil War Diary of Sidney George Fisher - Fisher, Sidney George (Fordham University Press, 2022)
"Invaluable...many insights into the life and thought of the nineteenth century.... [Fisher's] comments are stimulating, often barbed....the narrative is smooth-flowing and fascinating."-American Historical Review "An important literary event....an invaluable historical source. Unexcelled." -Pennsylvania History "Fisher was an astute and acerbic commentator on politics and society in Philadelphia, Washington, and the country as a whole during the Civil War. While legal, historical, and literary scholars will mine this diary for its penetrating insights, lovers of history will delight in Fisher's ability to record the "idian and the monumental with clarity, force, and lasting effect."-Herman Belz, University of Maryland "An indispensable source for the Northern home front during the Civil War."-Mark E. Neely, Jr., The Pennsylvania State University An aristocratic member of a prominent Philadelphia family, Sidney George Fisher (1809-1871) was a prolific man of letters.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: BIOGRAPHY & AUTOBIOGRAPHY / Historical